Determination of The Optimum pH and Enzyme Ratio for Starch Hydrolysis Test and Characterization of Steamed, Baked, and Fried Wheat Doughs - Setya Budi Muhammad Abduh; V. Priyo Bintoro; Nurwantoro Nurwantoro; Vitus Dwi Yunianto; Yoyok Budi Pramono (Journal of Applied Food Technology, 2023)
Digestibility is the most important nutritional functionality of starchy foods. Unfortunately, in Indonesia, this functionality has not been extensively studied due to the relatively challenging methods involving enzymes. This research aims to determine the optimal pH and enzyme ratio of α-amylase (AA) and glucoamylase (GA) for starch hydrolysis tests and apply them to characterize steamed, baked, and fried wheat doughs. For optimization, hydrolysis was carried out at 37 °C with an enzyme-to-substrate ratio (E/S) of 100 mL/g for 120 min. Samples of wheat dough obtained from three major dough producers in Banyumanik, Semarang, Indonesia was then tested for starch hydrolysis, texture, chemical analyses, sensory, and hedonic test. The collected data were analysed using principal component analysis (PCA). Under the determined conditions, the optimal pH and AA/GA ratio were found to be 6.6 and 0.5. Regarding quality of processed doughs, the steamed dough exhibited a cohesive texture, a soft sensory profile with a pleasant aroma, sweet taste, and was most preferred by the panellists. The baked dough was hard in texture, high in ash content, and brown in colour. The fried dough poses high starch hydrolysis, chewy texture, adhesion, solid particles, protein content, and relatively high lipid. The sensory evaluation indicated that the fried dough poses an oily, rancid, foreign aroma, and bitter and salty taste. It can be concluded that at a temperature of 37 °C, an enzyme-to-substrate ratio of 100 mL/g, and a reaction time of 120 min, the optimal starch hydrolysis of processed wheat dough can be achieved at a pH of 6.6 and an AA/GA ratio of 0.5. Furthermore, steaming resulted in a unique property of dough compared to the baked and fried, while the latter two yielded products with similar properties.